ANALISIS KINERJA DAN STRATEGI PENGEMBANGAN KOPERASI PERTANIAN SEANDANAN KABUPATEN PESAWARAN - Muhammad Rizqi Mubarok; Dyah Aring Hepiana Lestari; Wuryaningsih Dwi Sayekti (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2023)
This research aims to analyze the cooperative performance, internal and external environment, and formulate the development strategies of Agriculture Cooperative Seandanan.  This research is taken at Agriculture Cooperative Seandanan in Pesawaran District, which is chosen purposively.  Furthermore, data of this research was collected in January 2019.  This research uses a case study method.  Respondents of this research are 13 people consist of administrators and members of cooperative, experts and regulators.  Data analysis methods used in this research are qualitative descriptive analysis, SWOT (Strengths, Weakness, Opportunities, and Threats) analysis, and Quantitative Strategic Planning Matrix (QSPM).  The results of this research showed that the performance of cooperative was included in the category of sufficient quality.  Internally, the cooperatives had the main strength that healthy and independent capital and finance, while the main weakness that was management function that were not managed optimally.  Externally, cooperative’s main opportunity was easy and fast loan procedures, although the main threat was the weak understanding of the community about cooperatives.  The priority strategies for developing cooperatives were maximizing the cooperative management functions to strengthen the cooperative image in the community, utilizing assets in the form of buildings to increase cooperative income, in addition to compiling and completing the unorganized administration of cooperatives and formulating a clear vision and mission. Key words: agriculture cooperative, QSPM, SWOT analysis